MILITARY THEMES IN CONTEMPORARY UKRAINIAN LITERATURE: HISTORICAL CHALLENGES AND ARTISTIC REALITY - Vivcharyk, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article explores military themes in the works of contemporary Ukrainian writers. It illustrates that military themes have permeated various genres and forms of literature. Among the most well-known authors who have published poetry collections are Pavlo Vyshebaba’s “Don’t Write to Me About the War”, Borys Humeniuk’s “Poems from the War”, Olena Huseynova’s “Superheroes”, Anastasia Dmytruk’s “This Is My and Your War”, Serhiy Zhadan’s “Templars”, Kateryna Kalytko’s “No One Knows Us Here, and We Know No One”, Maksym Kryvtsov’s “Poems from a Gun Slot”, and Bohdan Tomenchuk’s “Embroider a Bulletproof Vest, Mom”. Among prose works, the most popular are Serhiy Zhadan’s “The Orphanage”, Yevhen Polozhiy’s “Ilovaisk”, Artem Chekh’s “Point Zero”, Vasyl Shkliar’s “Black Sun”, Maryna Hrymnych’s “Return from the War”, and Max Kidruk’s “Don’t Look Back and Keep Silent”. The article argues that realism and documentary elements are linked to the authors’ efforts to convey real facts and testimonies from both military personnel and civilians who suffered, as well as their experiences. Elements of romanticism, as a rule, emphasize noble ideals and the capacity for self-sacrifice. Dramatic works about the war are represented by authors such as Natalia Vorozhbyt’s “Bad Roads”, Oleksandr Gavrosh’s “Mariupol Drama”, Serhiy Zhadan’s “Bread Armistice”, Ned Nezhdana’s “Pussy on the Memory of Darkness” and others. Overall, the ideological and aesthetic analysis of works on military themes indicates that they often raise the issue of self-sacrifice for others, the preservation of national identity, historical memory, and culture. Writers also seek to convey psychological experiences, reflect the tragedy of war through the depiction of individual lives, and describe not only the heroic but also the tragic aspects of war. The article points out that works on military themes often touch on the issue of loss and the preservation of memory about people who become part of a larger historical process.